PARTISIPASI POLITIK DALAM KETERBUKAAN INFORMASI PUBLIK Studi Kasus Interaksi Pattiro dengan Pemerintah Kota Semarang - BISRI, ZAINI (Program Magister Ilmu Politik, Universitas Diponegoro, 2012)
Abstract Freedom of information enhance a new momentum to realize good governance and to promote democratic government system in Indonesia. By the Law 14/2008, citizen access to information has declared as part of freedom of human being. Access to public information get the law guarantee and its mechanism ruled explicitly. Moreover, in the Freedom of Information Act the political participation is mentioned clearly as one of its goal. This study try to analyzed freedom of information impact on community political participation through case study of Pusat Telaah dan Informasi Regional (Pattiro) interaction with Semarang Local Government. Keywords: Freedom of information, political participation, public institution, good governance, democracy.